The Role of Social Media in Observing Consumer Behavior in Decision Making in Choosing Barbershop Services - Kusuma, Sitta; Madiistriyatno, Harries; Listiorini, Dewi (Raudhah Publisher, 2025)
This study aims to explore the role of social media in influencing consumer behavior in choosing barbershop services. Qualitative research methods are used with a focus on data collection through in-depth interviews and social media content analysis. Participants in this study were barbershop service consumers who actively use social media to search for information and recommend services. The results of this study reveal that social media has a significant role in shaping consumer perceptions of the quality of barbershop services, as well as influencing consumer decisions in choosing barbershop services. These findings highlight the importance of a strong online presence and a good reputation on social media for barbershop business owners. The practical implication of this study is the need for a digital marketing strategy that is integrated with reputation management to increase consumer appeal and trust in barbershop services.